A DECADE OF SHARK DIVING MARINE TOURISM IN MOROTAI, NORTH MOLUCCAS, INDONESIA - Nasywa Nabilah; Maria Holy Octavia Sitorus; Aishah Gray; Darmawan Ahmad Mukharror (Politeknik Pariwisata Makassar, 2025)
Shark diving has emerged as one of the most significant forms of marine tourism worldwide, providing both economic opportunities and conservation challenges for coastal communities. This study examines a decade of shark diving tourism in Morotai, North Moluccas, Indonesia, focusing on its growth trajectory, ecological implications, and socio economic contributions. Data were collected from local tourism agencies, diver operators, and secondary records covering the period 2013–2025. The findings indicate that shark diving tourism in Morotai has expanded steadily, with an average annual increase in visitor numbers exceeding regional marine tourism growth rates. Economically, the activity has contributed substantially to local livelihoods through employment and revenue generation, while also stimulating small-scale businesses such as homestays and dive shops. However, challenges remain in terms of regulating diver shark interactions, ensuring ecosystem sustainability, and balancing conservation goals with tourism development. The case of Morotai illustrates the potential of shark-based ecotourism to foster sustainable blue economy initiatives in Indonesia, provided that appropriate management strategies, stakeholder engagement, and long-term monitoring frameworks are implemented.